The position of teaching materials on the monitor and its effect on the e-learning success - Žufić, Janko; Ružić-Baf, Maja; Zarevski, Predrag (2011)
There are various elements in designing e-teaching materials that could have an impact in raising the efficiency of e-learning. This paper is based on the experiments aiming to investigate whether there are certain positions on the monitor in which students are able to better perceive and remember e-teaching materials. Our research was carried out at the Juraj Dobrila University of Pula. Participants were first year students attending the teacher education programme (aged 19.5 – 20.5). The research design included two pre-experimental groups and one experimental group. The monitor was virtually divided into 24 zones. Students read the teaching material displayed on the screen ; in each reading four texts in different positions were used. The relative ease/difficulty of remembering the text was taken into account by introducing different ponders to each text. Regarding the memory efficiency, our results show statistically significant differences between certain screen positions (these differences ranged from +33.8% to -45.7% from the average result).
Projekt MZOS
ENG